RESPON ULAMA NAHDLATUL ULAMA MADURA TERHADAP FATWA MAJELIS ULAMA INDONESIA TENTANG WAKAF UANG - Harisah, Harisah; Gultom, Mitra Sami; Hosen, Muhammad Nadratuzzaman; Kusairi, Ah.; Ahmad, Azlin Alisa (Ekonomi Islam, 2024)
This research was aimed at examining the response made by the ulama (Islamic religious scholars) of the Madura Branch of the NU and to find out their reactions to the MUI fatwa concerning cash wakaf. This research was classified as qualitative. The sample for this research consisted of 101 religious scholars of the Madura branch of the NU. The research was conducted in the form of surveys and interviews with these Madura NU members, to ascertain their arguments. The results of the research obtained showed convincingly that the majority of NU religious scholars accept and agree with the MUI Fatwa concerning cash wakaf, in that the response “agree” (Setuju – S) received the highest percentage return for all items, recording positive results between 40% and 60%, whilst the percentages for the response “strongly agree” (sangat setuju - SS) was the second strongest, receiving between 19% and 48% support. Based upon the results of the interviews conducted by the researchers with the NU Madura theologians, it was their opinion that the MUI Fatwa concerning cash wakaf fulfils the requirements of Islamic religious law. Not only that, but these scholars were also of the opinion that a cash wakaf can be a beneficial social instrument and may assist in overcoming social problems in their regions. The implication of this study is that the validity of the MUI fatwa can be widely accepted among local scholars, providing a strong legal foundation for the development of cash waqf in Indonesia, particularly in Madura. This fatwa is not only recognized as valid according to Islamic law, but also serves as a basis for the acceptance of cash waqf by the public as a legitimate and effective charitable instrument Keywords: Nahdhatul Ulama’, Fatwa Commission, Cash Wakaf, Madura.